Gesture controlled wheelchair for quadriplegic children - Jain, Yash M.; Labde, Saurabh S.; Karamchandani, Sunil (2016 3rd International Conference on Systems and Informatics (ICSAI), 2016)
This paper presents a simple but efficient method to implement hand gesture recognition which promises a framework for the physically impaired people. Gestures are used universally to express emotions and thoughts. Using these gestures it is possible to control the wheelchair in an efficient way which is natural and convenient unlike controlling it by a computer, which can be an arduous task. It has been demonstrated that young children can readily learn to communicate with gestures before they learn to talk. This model involves the use of micro-electromechanical sensors, micro-controllers, transmitter-receiver pair for wireless transmission of data and the wheelchair for the prototype. This system is highly efficient as compared to the other conventional methods. Based on the data from either the accelerometer or the touchpad, the movements of the wheelchair is controlled. This paper presents a new gesture controlled wheelchair with many advantages such as reduced complexity, easy controlling, low cost and great reliability compared to other conventional wheelchairs. The working and assembly of this system will be explained in the paper.